Immunological effect of sparfloxacin in goats - Singh, Vivek Pratap; KUMAR NIRALA, RAMESH; GOND, V K; GANGWAR, S K; ANJANA, K; JAYACHANDRAN, C; SINGH, M K; SINGH, R P; SINGH, V P (The Indian Journal of Animal Sciences, 2021)
In the present study, the immunological effects of a fluoroquinolone, sparfloxacin, were studied in goats after multiple i.m. administration. Three groups of goats (4 goats in each) were selected. Group I consisted of saline control, Group II contained animals with antigen (Ag) control [2 ml of 7% sheep red blood cell (SRBC), Ag given on 1st day as sensitizing dose and on 10th day as challenging dose] and Group III consisted of animals exposed to sparfloxacin and SRBC Ag (Sparfloxacin @ 5 mg/kg i.m. daily for 7 days during sensitizing and challenging period and SRBC as given in Group II). The blood samples were collected on 1, 7, 10, 14, 21, 28, 35 and 42 days of the experiment. The immunological parameters evaluated were haemagglutination (HA) test for humoural immune response (HIR) whereas delayed type hypersensitivity (DTH) for evaluating cell mediated immune response (CMIR). DTH was assessed by injecting 1-chloro-2,4-dinitrobenzene (DNCB) and purified protein derivative (PPD) in the skin of the neck region as well as by absolute lymphocyte count. There was no significant effect of sparfloxacin on humoural immune response as assessed by HA test. DTH assessed by DNCB mitogen was significantly higher in sparfloxacin treated group as compared to antigen treated whereas in case of PPD mitogen there was no significant effect of the drug. Absolute lymphocyte count differed significantly in sparfloxacin treated group (6499.75±19.87) with antigen treated group (5485.00±19.87). Thus, it can be concluded that sparfloxacin has some immunomodulatory effect with respect to cell mediated immune response in goats.In the present study, the immunological effects of a fluoroquinolone, sparfloxacin, were studied in goats after multiple i.m. administration. Three groups of goats (4 goats in each) were selected. Group I consisted of saline control, Group II contained animals with antigen (Ag) control [2 ml of 7% sheep red blood cell (SRBC), Ag given on 1st day as sensitizing dose and on 10th day as challenging dose] and Group III consisted of animals exposed to sparfloxacin and SRBC Ag (Sparfloxacin @ 5 mg/kg i.m. daily for 7 days during sensitizing and challenging period and SRBC as given in Group II). The blood samples were collected on 1, 7, 10, 14, 21, 28, 35 and 42 days of the experiment. The immunological parameters evaluated were haemagglutination (HA) test for humoural immune response (HIR) whereas delayed type hypersensitivity (DTH) for evaluating cell mediated immune response (CMIR). DTH was assessed by injecting 1-chloro-2,4-dinitrobenzene (DNCB) and purified protein derivative (PPD) in the skin of the neck region as well as by absolute lymphocyte count. There was no significant effect of sparfloxacin on humoural immune response as assessed by HA test. DTH assessed by DNCB mitogen was significantly higher in sparfloxacin treated group as compared to antigen treated whereas in case of PPD mitogen there was no significant effect of the drug. Absolute lymphocyte count differed significantly in sparfloxacin treated group (6499.75±19.87) with antigen treated group (5485.00±19.87). Thus, it can be concluded that sparfloxacin has some immunomodulatory effect with respect to cell mediated immune response in goats.